If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(2x + -1) = 26 Reorder the terms: 2(-1 + 2x) = 26 (-1 * 2 + 2x * 2) = 26 (-2 + 4x) = 26 Solving -2 + 4x = 26 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 4x = 26 + 2 Combine like terms: -2 + 2 = 0 0 + 4x = 26 + 2 4x = 26 + 2 Combine like terms: 26 + 2 = 28 4x = 28 Divide each side by '4'. x = 7 Simplifying x = 7
| 0.25y-0.01x=0.005 | | y=12-9 | | 6(3.14)=w-6(3.14) | | ((x-1)/3)-2=((x-5)/4) | | 2x+18y=18 | | 3x-11=2x+33 | | 14-b=8 | | -4+3x=7x+x+14x-8x | | 65=-6-x | | 81=x+181 | | 6/10-2/100 | | V-10=-19 | | -4+3x=7x+x+14-8x | | 9a-6=8a+1 | | 2x+2x+x+3x+3=24 | | 2x+0=5y-0 | | 5x+6=9x+3+8x | | 7bf^4-7bk^4= | | 6u(-5u^4)=0 | | 2a-1=3(a+1)+7a+5 | | X+4+5x+3+4x=21 | | (y^-1/4)^1/6 | | 9-3v=0 | | 17x-36=12x+7 | | x+8=-72 | | 2(x-6)=3(x-4) | | y^(3/2)-10y | | 18=x/7 | | 66=1.5x | | -5(6y-6)-y=-3y(y-5) | | 16a^4+36a^3b-10a^2b^2= | | 5(7n-4)-3= |